Wave Breaking for the Rotational Camassa–Holm Equation on the Circle - Rendong Chen (Journal of Mathematics)
In this paper, we consider the rotational Camassa–Holm equation on the circle. Sufficient conditions on the initial data to guarantee wave breaking are established.